A new Dyckia species (Bromeliaceae, Pitcairnioideae) from Brazilian Central-West region, Pantanal Mato-Grossense - Pereira, Eddie Esteves; Gouda, Eric John (Phytotaxa, 2018)
A new species of Dyckia from the municipality of Porto Murtinho, in the state Mato Grosso do Sul, Brazil is described and illustrated here and compared with two of the closest related species known. Its conservation status is discussed.